Sirtuin 3 Protects Lung Adenocarcinoma from Ferroptosis by Deacetylating and Stabilizing Mitochondrial Glutamate Transporter Solute Carrier Family 25 Member A22 - Xiangyun Wei; Tiange Wang; Zhengcao Xing; Qinyun Shi; Jianmin Gu; Qiuju Fan; Hao Wang; Bin Chen; Jinke Cheng; Rong Cai (Antioxidants)
Solute carrier family 25 member A22 (SLC25A22) is a glutamate transporter in the inner mitochondrial membrane that is known to suppress ferroptosis in pancreatic ductal adenocarcinoma (PDAC). Sirtuin 3 (SIRT3) is the main mitochondrial deacetylase, and we previously demonstrated that targeting SIRT3 sensitized glioblastoma to ferroptosis by promoting mitophagy and inhibiting SLC7A11. The purpose of this study was to analyze the effect of SIRT3-mediated deacetylation of mitochondrial SLC25A22 on RAS-selective lethal 3 (RSL3)-induced ferroptosis in lung adenocarcinoma (LUAD). We found that the expression of SLC25A22 and SIRT3 had a high positive correlation and that their expression was greater in LUAD tissues than in adjacent tissues. The RSL3-induced ferroptosis of LUAD led to upregulation of SLC25A22 and SIRT3, and SIRT3 protected RSL3-induced LUAD from ferroptosis in vitro and in vivo. At the molecular level, SIRT3 bound with SLC25A22 and deacetylated this protein. Targeting SIRT3 enhanced the acetylation of SLC25A22, decreased its ubiquitination, and promoted 26S proteasome degradation in LUAD cells. Therefore, our results demonstrated that SIRT3 protected LUAD cells from RSL3-induced ferroptosis, and this effect is at least partially due to its deacetylation of SLC25A22, revealing that the SIRT3-SLC25A22 axis has an important role in regulating the ferroptosis of LUAD cells.